A preliminary study on electricity affordability and willingness to pay (WTP) on maximum demand (MD) charge among residential electricity customers in Malaysia - Zainudin W.N.R.A.; Wan Abdullah W.M.Z.; Ramli N.A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by Scopus